2020
DOI: 10.3390/rel11050219
|View full text |Cite
|
Sign up to set email alerts
|

Religion and Peace—Anatomy of a Love–Hate Relationship

Abstract: Human history is filled with numerous examples—both past and present—that make religion and violence appear to be best friends. Ever since the events surrounding 9/11, religiously inspired violence has been considered one of the most pressing issues of our times (cf. Juergensmeyer 2017; Kimball 2008). While the conflictive dimensions of religion are still indisputably at the forefront of public and political attention, religion’s significant resources for peace and reconciliation gain increasing attention as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This prevalence is largely due to the expansion of what is often termed 'modern-liberal' peace, as disseminated through historical processes of colonialism and developmental ideologies (Daley 2014). In the context of religions, peace may involve fostering interfaith dialogue, promoting religious tolerance and working towards social justice and reconciliation (Schliesser 2020;Osajie 2021).…”
Section: Relevance Of Promoting Human Dignity For Fostering Peace And...mentioning
confidence: 99%
See 1 more Smart Citation
“…This prevalence is largely due to the expansion of what is often termed 'modern-liberal' peace, as disseminated through historical processes of colonialism and developmental ideologies (Daley 2014). In the context of religions, peace may involve fostering interfaith dialogue, promoting religious tolerance and working towards social justice and reconciliation (Schliesser 2020;Osajie 2021).…”
Section: Relevance Of Promoting Human Dignity For Fostering Peace And...mentioning
confidence: 99%
“…Scholars in peace and conflict studies, sociology, political science and other related fields have contributed to the understanding of these concepts (Galtung 1990;Gleditsch et al 2014). Yet, definitions of violence and peace can also be influenced by religious beliefs, practices and teachings (Basedau and Koos 2015;Schliesser 2020). This makes it crucial to consider multiple perspectives and engage in interdisciplinary dialogue while studying violence and peace.…”
Section: Relevance Of Promoting Human Dignity For Fostering Peace And...mentioning
confidence: 99%
“…Religious leaders might influence voters because they are role models in society. Religious leaders, according to Schliesser (2020), are role models for the community. As moral authorities, they act as influencers by shaping social values.…”
Section: Introductionmentioning
confidence: 99%
“…Conflicts are frequently driven by discrimination and generate massive numbers of refugees and internally displaced persons (IDPs) as they flee from persecution and violence, whilst individuals or groups may be targeted for their identity or face insecurity during community activities. Research in conflict resolution and international peace-building has found that ignoring dynamics of religious pluralism can become a source of conflict if not addressed sensitively (Schliesser 2020). Further data shows that violence against religious minorities during conflict can also make them vulnerable to further attacks in refugee settings (see USCIRF 2013a, 2013b).…”
Section: Introductionmentioning
confidence: 99%